Genetic risk of type 2 diabetes in populations of the African continent: A systematic review and meta-analyses. (April 2016) - Yako, Yandiswa Y.; Guewo-Fokeng, Magellan; Balti, Eric V.; Bouatia-Naji, Nabila; Matsha, Tandi E.; Sobngwi, Eugene; Erasmus, Rajiv T.; Echouffo-Tcheugui, Justin B.; Kengne, Andre P.
Highlights: This is a first systematic review and meta-analysis of genetic studies of T2D in Africa. Available genetic studies of T2D in Africa mostly originate in northern Africa. The role of TCF7L2 and KCNQ SNPs, which showed greatest effect in Europeans and Asians respectively, is unclear in Africans according to our meta-analysis. Larger-scale studies will help understanding the genetic mechanisms of type 2 diabetes in Africa. Abstract: Background: Type 2 diabetes (T2D) is growing faster in Africa than anywhere else, driven by the dual effects of genetic and environmental factors. We conducted a systematic review and meta-analyses of published studies on genetic markers of T2D in populations within Africa. Methods: Multiple databases were searched for studies of genetic variants associated with T2D in populations living in Africa. Studies reporting on the association of a genetic marker with T2D or indicators of glycaemia were included. Data were extracted on study design and characteristics, genetic determinants, effect estimates of associations with T2D. Findings: Overall, 100 polymorphisms in 57 genes have been investigated in relation with T2D in populations within Africa, in 60 studies. Almost all studies used the candidate gene approach, with >88% published during 2006–2014 and 70% (42/60) originating from Tunisia and Egypt. Polymorphisms in ACE, AGRP, eNOS, GSTP1, HSP70-2, MC4R, MTHFR, PHLPP, POL1, TCF7L2, and TNF-α gene were found to be associated with T2D, with overlapping effect on various cardiometabolic traits. The polymorphisms investigated in multiple studies mostly had consistent effects across studies, with only modest or no statistical heterogeneity. Effect sizes were modestly significant [e.g., odd ratio 1.49 (95%CI 1.33–1.66) for TCF7L2 ( rs7903146)]. Underpowered genome-wide studies revealed no diabetes risk loci specific to African populations. Interpretation: Current evidence on the genetic markers of T2D in African populations mostly originate from North African countries, is overall scanty and largely insufficient to reliably inform the genetic architecture of T2D across Africa.